COVID-19 POPULISM CHALLENGES AND CHINA’S FINANCIAL LAW RESPONSES: THREE EMERGING CASE SCENARIOS - Wei Shen; Carrie Shu Shang; Li Fang (Bank Indonesia, 2023)
China’s increasing engagement in international governance has had significant ramifications in international rule-making and institutional build-up. The post-COVID-19 era has seen a rise of populism in China, as well as an elevation of China’s significance in international governance. This article offers a new perspective on China’s growing influence in the midst of resurgent populism, by focusing on three case scenarios: defending state liability in public health crisis lawsuits, championing financial multilateralism, and an emerging digital currency landscape. The argument made here is that China’s status as a rising power has led it to advocate for international rules, standards, and institutions in a de-Americanised and anti-populist manner.